Taylor series remainder’s kernel evaluation in tridiagonal enhanced multivariance products representation (TKEMPR) perspective - Gürvit, Ercan; Okan, Ayla; Baykara, N. A. (Author(s), 2018)
The intended work uses the TKEMPR method which decomposes a linear integral operator on univariate functions by using high dimensional modelling with the basic idea to use repeated bivariate Enhanced Multivariance Products Representation (EMPR) technique which is called Tridiagonal Kernel Enhanced Multivariance Products Representation (TKEMPR). It uses EMPR bivariate function decomposition consecutively such that in each step the remainder term is expanded to again a bivariate EMPR but with different support functions.